Parámetros poblacionales de Zulia carbonaria (Hemiptera: Cercopidae) sobre Brachiaria ruziziensis - Rodríguez Chalarca, Jairo; Peck, DC (2006)
To complement biological studies developed at CIAT on grass-feeding spittlebugs (Hemiptera: Cercopidae), a life table was established for the specific case of Zulia carbonaria (Lallemand). The cohort life table was conducted in the laboratory (27°C, 100% RH, continual darkness) for the eggs and in the screenhouse (19.5/29.5°C min./max., RH min. 56.3%) for the nymphs and adults. The survival exhibited by Z. carbonaria was 53.4% (egg-adult). The total mortality exhibited by the immature stages of Z. carbonaria was 46.4% divided in 10.1 and 36.3% for the eggs and nymphs, respectively, with a killing-power (kx) of 0.27. For the fertility table, the mean longevity of females was 29.3 days, with a mean fecundity of 125.8 ± 82.9 eggs/female and a fertility of 97.9%. The generational time (T) was 67.4 days, with a net reproductive rate (Ro) for (T) of 33.6 times. The intrinsic rate of natural increase (rm) showed that Z. carbonaria produces 0.05 females/day during the generational time. In addition, it was determined that the females presented a finite rate of multiplication (?) of 1.05 females/day. This information is the first of its kind for spittlebug species in Colombia, and constitutes an appropriate tool to determine the quality of populations obtained from artificial colonies or under different habitat and host plant conditions.